WRL68-CYP3A4 and WRL68-CYP2C9 mutagenesis in vitro drug metabolism models for the assessment drug-herb interactions / Nurliana Abd Mutalib - Abd Mutalib, Nurliana (2022)
In vitro screening of drug interactions is one of the most important steps in early drug discovery. Inhibition and stimulation of the phase 1 metabolism enzymes known as CYP450 isozymes is the most prominent form of drug interactions. More reliable and high specificity in vitro models are needed to improve the predictions of clinical metabolism-based drug interactions related to CYP450 and its variants. The use of herbal remedies in complementary and alternative medicine has been a popular practice all around the world with little information regarding its interaction with common drugs. Potential drug-herb interaction due to co-treatment of herb and conventional drug has become an issue of concern in healthcare practice. Therefore, in vitro screening of medicinal plant for its potential CYP450 related drug-herb interaction using a reliable system is an important step in the evaluation of safety of use. This study aimed to develop a metabolism-based cell model for in vitro assessment of drug interactions related to two major CYP450 isozymes, which are CYP3A4 and CYP2C9. A foetal liver cell line, WRL 68, was evaluated for its hepatic marker genes, basal CYP450 and the redox partners expression, and was found suitable as a cell host for the models. Using an optimized polyethylenimine (PEI) mediated transient transfection protocol, WRL 68 cells were incorporated with CYP3A4 and CYP2C9 genes carrying plasmids to overexpress the isozymes. Without alteration of basal redox partners expression, optimum CYP3A4 and CYP2C9 overexpression were achieved at 48 hours post transfection which were confirmed by qRT-PCR and western blot analyses. Here, two HPLC-DAD methods were developed and validated for quantification of 6β hydroxytestosterone and 4’-hydroxydiclofenac, the metabolite from enzymatic reactions of CY3A4 and CYP2C9, respectively. WRL68-CYP3A4 and WRL68- CYP2C9 models were successfully developed and evaluated for kinetic parameters which were found in good agreement with data reported in the literature. These models were also developed for SNPs variants of the isozymes. WRL68-CYP3A4*4, WRL68- CYP3A4*18, WRL68-CYP2C9*2 and WRL68-CYP2C9*3 systems were successfully developed as in vitro models and can be used to study metabolic activities and drug interactions on different enzyme variants. Finally, the WRL68-CYP2C9 and its variants models were utilized to investigate inhibitory drug-herb interactions by Clinacanthus nutans towards CYP2C9. In this study, ethanolic extract of C. nutans leaves was prepared. Five common flavonoids of C. nutans which are schaftoside, isoorientin, orientin, vitexin and quercetin were identified from HPLC-UV phytochemical profiling of the extract. C. nutans extract and quercetin exhibit varied potency in inhibiting different CYP2C9 variants. From the evaluation of kinetic parameters as well as Lineweaver-Burk plots constructed, both C.nutans extract and quercetin inhibited wild type CYP2C9 in an uncompetitive manner. Inhibition level of both inhibitors were varied on CYP2C9*2 and CYP2C9*3 in comparison to wild type CYP2C9. In conclusion, the metabolism-based cell models for in vitro assessment of drug interactions related to CYP3A4 and CYP2C9 variants has been successfully developed.